The First Record of the Balkan Endemic Caddisfly Drusus osogovicus Kumanski, 1980 (Trichoptera: Limnephilidae) in the Republic of North Macedonia, with DNA barcoding of the species and comments on its ecology and distribution - Hinić, J., Slavevska-Stamenković, V., Ibrahimi, H., Bilalli, A., Musliu, M., Kučinić, M., Beerman, A. & Lesse, F. (My University, 2020)
The Balkan endemic caddisfly species Drusus osogovicus Kumanski, 1980, previously known only from the Bulgarian part of the transboundary Osogovo Mountain, is reported from the Republic of North Macedonia for the first time. The species is recorded at four localities in the country: two localities in the NorthMacedonian part of Osogovo Mountain and two localities in the Karadak (Skopska Crna Gora) Mountain. In addition to the morphology-based taxonomic analyses of male and female genitalia, the identification is confirmed on the basis of DNA barcoding (partial sequence of mitochondrial cytochrome oxidase I gene). The distribution of the species is restricted to low-temperature (6–9°C) mountain springs, streams and rivers at altitudes of 1380–1608 m. The emergence period of D. osogovicus is identified as May – July, suggesting one-year life cycle of this species
Keywords: Drusinae, Balkan Peninsula, freshwater biodiversity, taxonomy, DNA